The RhoA Effector mDia Is Induced During T Cell Activation and Regulates Actin Polymerization and Cell Migration in T Lymphocytes - Vicente-Manzanares, Miguel; Rey, Mercedes; Perez-Martinez, Manuel; Yanez-Mo, Maria; Sancho, David; Cabrero, Jose Roman; Barreiro, Olga; de la Fuente, Hortensia; Itoh, Kazuyuki; Sanchez-Madrid, Francisco (The Journal of immunology (1950), 2003)
Regulation of actin polymerization is critical for many different functions of T lymphocytes, including cell migration. Here we show that the RhoA effector mDia is induced in vitro in activated PBL and is highly expressed in vivo in diseased tissue-infiltrating activated lymphocytes. mDia localizes at the leading edge of polarized T lymphoblasts in an area immediately posterior to the leading lamella, in which its effector protein profilin is also concentrated. Overexpression of an activated mutant of mDia results in an inhibition of both spontaneous and chemokine-directed T cell motility. mDia does not regulate the shape of the cell, which involves another RhoA effector, p160 Rho-coiled coil kinase, and is not involved in integrin-mediated cell adhesion. However, mDia activation blocked CD3- and PMA-mediated cell spreading. mDia activation increased polymerized actin levels, which resulted in the blockade of chemokine-induced actin polymerization by depletion of monomeric actin. Moreover, mDia was shown to regulate the function of the small GTPase Rac1 through the control of actin availability. Together, our data demonstrate that RhoA is involved in the control of the filamentous actin/monomeric actin balance through mDia, and that this balance is critical for T cell responses.